Building component maintenance/ repair management: An economic analysis simulation - Amani, Nima; Nasly, Mohamed Ali; Hosseini, Seyedmohsen (Trans Tech Publications, 2011)
Starting, implementation, and operation of building facilities system are very vital, especially under limited budget. To component repair cost decisions, suitable assessment, and accurate prediction of the condition of assets are essential. The purpose of this study is at supporting the condition assessment and predicting the future of component condition by NCES condition metrics. This paper reflects on the NCES condition index process in maintenance and repair system of building components by research in similar subjects and looks specifically at the use of NCES condition index (CI) as a development tool. The result of research can be used as a guide to assist component managers and building owners to make suitable decisions about component appropriate maintenance based on limited budget during its service life.